2018
DOI: 10.1155/2018/4302726
|View full text |Cite
|
Sign up to set email alerts
|

Harmful Roles of TLR3 and TLR9 in Cardiac Dysfunction Developing during Polymicrobial Sepsis

Abstract: We determined the roles of TLR3 and TLR9 in adverse events of polymicrobial sepsis, with a focus on development of septic cardiomyopathy, progression of which we have recently shown to be complement- and histones-dependent. So Wt, TLR3-knocked out (K.O.), and TLR9-K.O. mice were subjected to polymicrobial sepsis following cecal ligation and puncture (CLP). In the absence of either TLR3 or TLR9, the intensity of echocardiogram (Echo)-Doppler dysfunction during development of cardiomyopathy was substantially red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Myocardial cells express TLR2, TLR3, TLR4, and TLR9 (Vallejo, 2011). A study by Fattahi et al (2018b) has shown that LVEF was increased and plasma pro-inflammatory cytokines (TNF-α, IL-1, IL-6) were decreased significantly in a mouse septic model with TLR9 and TLR3 deletion, suggesting that TLR9 and TLR3 activation is associated with dysfunction of heart in sepsis. TLR4 can bind to LPS, and then cause the release of a variety of inflammatory factors, finally insults in cardiac dysfunction (Vallejo, 2011).…”
Section: Toll-like Receptors In Cardiomyocytesmentioning
confidence: 99%
“…Myocardial cells express TLR2, TLR3, TLR4, and TLR9 (Vallejo, 2011). A study by Fattahi et al (2018b) has shown that LVEF was increased and plasma pro-inflammatory cytokines (TNF-α, IL-1, IL-6) were decreased significantly in a mouse septic model with TLR9 and TLR3 deletion, suggesting that TLR9 and TLR3 activation is associated with dysfunction of heart in sepsis. TLR4 can bind to LPS, and then cause the release of a variety of inflammatory factors, finally insults in cardiac dysfunction (Vallejo, 2011).…”
Section: Toll-like Receptors In Cardiomyocytesmentioning
confidence: 99%
“…Regarding other TLRs, we have also shown that the full development of cardiac dysfunction developing in septic mice requires the presence of both TLR3 and TLR9 ( 48 ). Septic mice with KO of either TLR3 or TLR9 have attenuated cardiac dysfunction during sepsis, but the precise pathways responsible for such changes are not currently known.…”
Section: Phases Of Polymicrobial Sepsismentioning
confidence: 99%
“…Septic mice with KO of either TLR3 or TLR9 have attenuated cardiac dysfunction during sepsis, but the precise pathways responsible for such changes are not currently known. However, in recent studies, cardiomyocytes (from normal mice) exposed to the histone mix showed release of LDH and the septic hearts showed release of proinflammatory cytokines (TNF, IL-6, and IL-1β) that are greatly diminished in hearts from TLR3 or TLR9 KO mice ( 48 ). Obviously, much more data are needed in terms of roles of TLRs in sepsis.…”
Section: Phases Of Polymicrobial Sepsismentioning
confidence: 99%
“…Other damaging features of histones is that they can directly cause cell damage and apoptosis and are very prothrombotic and proinflammatory . Several studies showed that histones bind to different TLRs (mainly TLR2 and TLR4) and interact with these receptors on various cell types . It should be mentioned that depending on the experimental setting and cell lines used, there are additional data about TLR2 or TLR4 being activated by histones.…”
Section: Mechanisms Of Histone‐induced Cell Damage In Sepsismentioning
confidence: 99%